Некоторые риски, возникающие в процессе присвоения цифровой ренты в условиях сотрудничества Республики Беларусь и Китайской Народной Республики - Голубцова, А. В. (БНТУ, 2024)
The article examines a new phenomenon for socio-economic systems – the «digital economy». It also presents the importance of digital technologies for Belarus and China, in particular the activities of the Great Stone Industrial Park. The risks and ways to solve problems in obtaining digital rent are discussed.